2014
DOI: 10.1016/j.gde.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The peopling of the African continent and the diaspora into the new world

Abstract: Africa is the birthplace of anatomically modern humans, and is the geographic origin of human migration across the globe within the last 100,000 years. The history of African populations has consisted of a number of demographic events that have influenced patterns of genetic and phenotypic variation across the continent. With the increasing amount of genomic data and corresponding developments in computational methods, researchers are able to explore long-standing evolutionary questions, expanding our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 122 publications
1
52
0
Order By: Relevance
“…As a result, the history of African green monkey populations reflects a similar pattern than those of the peopling of the African continent (see Campbell et al. for an in‐depth review). The split of C. a. aethiops from the other four populations around 164–195 kya resembles the divergence estimate for the earliest population split in the modern human lineage on the African continent (i.e., between the ancestors of Khoesan‐speaking San hunter‐gatherers and other sub‐Saharan Africans >100 kya (Schuster et al.…”
Section: Resultsmentioning
confidence: 98%
“…As a result, the history of African green monkey populations reflects a similar pattern than those of the peopling of the African continent (see Campbell et al. for an in‐depth review). The split of C. a. aethiops from the other four populations around 164–195 kya resembles the divergence estimate for the earliest population split in the modern human lineage on the African continent (i.e., between the ancestors of Khoesan‐speaking San hunter‐gatherers and other sub‐Saharan Africans >100 kya (Schuster et al.…”
Section: Resultsmentioning
confidence: 98%
“…The modern human species originated in East Africa approximately 200 000 years ago and subsequently extended its range throughout the African continent. Some 75 000 years ago , modern humans began to migrate out of Africa and gradually extended the human range to include all the continents, except Antarctica, and many of the offshore and oceanic islands.…”
Section: Co‐evolution Of Kir and Hla Class I In Modern Humansmentioning
confidence: 99%
“…2). African populations present the highest levels of diversity worldwide, and the diversity of non-African populations decreases with increasing distance from Africa (Abecasis et al, 2010, 2012; Campbell et al, 2014), attesting to the occurrence of bottlenecks and founder events during their migrations across the globe (Jakobsson et al, 2008; Henn et al, 2012). Recent studies based on whole-genome sequencing have shown that all contemporary non-Africans are descended from a single population that left Africa less than 60,000 yr ago (Malaspinas et al, 2016; Mallick et al, 2016).…”
Section: Reconstructing the Genomic History Of Homo Sapiensmentioning
confidence: 99%
“…Genetic studies have also revealed substantial population structure (i.e., subdivision) within continents. In sub-Saharan Africa, population structure is correlated with geography, language family, and mode of subsistence (Henn et al, 2012; Campbell et al, 2014; Patin et al, 2014), whereas, in Europe, genetic diversity is strongly driven by geography, and population structure is detectable within even very small geographic areas (Novembre et al, 2008). The quantification of population structure has important implications for studies of disease, as it must be carefully controlled for in genome-wide association studies (GWAS).…”
Section: Reconstructing the Genomic History Of Homo Sapiensmentioning
confidence: 99%